Breeding a series of new rice restorer lines with blast resistance and low‐to‐intermediate apparent amylose contents by integrating marker‐assisted and phenotypic selection. Issue 11 (4th August 2021) - Qin, Peng; Jiang, Nan; Hu, Xiaochun; Zhu, Yuxuan; Deng, Zhao; Bai, Zhenan; Fu, Jun; Zhang, Xuanwen; Wang, Kai; Chen, Sheyuan; Yang, Yuanzhu
Abstract: Hybrid rice, as one of the most successful crops exploiting heterosis, has greatly contributed to global food security. Due to its high‐yield potential, approximately half of the rice‐growing area in China is planted with hybrid rice varieties. However, the extreme vulnerability of hybrid rice to various diseases and poor grain quality pose great challenges to rice breeders. Here, we report the development of five new restorer lines pyramiding the broad‐spectrum blast resistance gene Pigm and low/intermediate amylose content‐associated gene Wx b by marker‐assisted and phenotypic selection. All these new restorer lines showed enhanced blast resistance in the disease nursery compared with the original restorer lines and had low‐to‐intermediate apparent amylose contents, ranging from 11.3% to 14.2%. Genetic background analysis based on next‐generation sequencing indicated that the proportion of Gumei 4 (donor of Pigm ) genome in the five new restorer lines ranged from 9.89% to 21.69%. Eight of their derived hybrid combinations, which exhibited better grain quality and higher levels of blast resistance, have been certificated for commercial release in different ecological regions of China. Among them, Jing‐Liang‐You 3189, Yue‐Liang‐You 3189, Jing‐Liang‐You 1074 and Long‐Liang‐You 3188 meet the national standards for superior‐quality rice in China. These results confirmed the success of developing elite restorer lines through marker‐assisted and phenotypic selection, and these new restorer lines have great potential in developing more elite hybrid rice combinations.